Fritidshemmets fysiska lärmiljö inomhus: möjligheter och begränsningar - Christina Grewell; Lena Boström (Educare)
Swedish School-age Educare Centers [SAECs] are predominantly integrated within primary schools, and studies have highlighted problems related to the physical learning environment. This study aims to investigate, analyze, and explain how the indoor physical learning environment constitutes opportunities and constraints from the pupils’ perspectives. The study was conducted through walk and talk conversations with pupils in four SAECs. The pupils’ descriptions were analyzed using a reflexive thematic analysis and interpreted through the theoretical frameworks of Sociology of Childhood, structuration theory and psychological ownership theory. The results show that the physical learning environment is a complex interplay between people and the physical, social, and organizational environment. Four themes, containing a duality of possibilities and constraints, were identified: variety and diversity; privacy protected places; premises and organization; and well-being and belonging. These themes relate to educational aspects, such as students’ agency, creativity, play, socialization, recovery, participation and sense of ownership. The study concludes that the design of the physical environment should not be too complex, as structural conditions limit the pupils’ freedom and agency. The findings underscore the importance of creating spaces that promote both independence and belonging for students.